The model of online al-da'wah al-fardiyyah - Ashaari, Muhammad Faisal; Abdul Ghani, Rozina (2010)
The emergence of the Internet as a most popular medium of communication that combines all elements of traditional media brought a new dimension to al-dacwah alfardiyyah as it can now be undertaken in cyberspace as well as face to face. This study proposes a model of online al-dacwah al-fardiyyah that incorporates the traditional approach of aldacwah al-fardiyyah which is based on face to face with a model of online communication. The traditional approach of aldacwah al fardiyyah is selected from the al-Dib's work (2002) while the model of online communication is selected from a model of online learning called as “e-moderating” developed by Salmon (2000). The main elements of the proposed model is based on socialization that should be directed into three levels namely dissemination, participation and mobilization.